PENERAPAN METODE EXAMPLE-NON-EXAMPLE DALAMPEMBELAJARAN KEANEKARAGAMAN HEWAN DI SMPN 2 TENGARAN KABUPATEN SEMARANG - Setyaningsih, Yuli; Rahyuningsih, Margareta; Priyono, Bambang (Journal of Biology Education, 2013)
The aims of this research was to determine the effectiveness of the application method Example Non Example on the activity and student learning outcomes at the Animal Diversity material in SMP N 2 Tengaran. This true experimental research design uses random subject design test design (post-test only control design) with 2-class samples are class VII G as a control class and class VII I as a experiment class. The technique sampling used is a convinence sampling technique. The percentage activity of students in the experimental class and control classes were 91.66% and 60.03%. The percentage of students in the classical mastery in experimental classes and control classes were 75.00% and 18.75%. T-test was used to examine the difference average of the learning outcomes between control class and experimental class. The results of t-test obtained tcount=7,22>ttable=1,67 with Î± = 5% and df = 66, so the average student learning outcomes in experimental classes are better than the control class. Based on these results can be concluded that the application of methods Example Non Example at the Animal Diversity material effective to increase the activity and student learning outcomes in SMP N 2 Tengaran Semarang regency landmarks.Â Penelitian ini bertujuan untuk mengetahui efektifitas penerapan metode Example Non Example terhadap aktivitas dan hasil belajar siswa pada materi Keanekaragaman Hewan di SMP N 2 Tengaran Kabupaten Semarang. Penelitian true experimental design ini menggunakan desain random subject test design (post-test only control design) dengan 2 (dua) kelas sampel yaitu kelas VII G sebagai kelas kontrol dan kelas VII I sebagai kelas eksperimen. Teknik pengambilan sampel yang digunakan adalah teknik Convinience Sampling. Persentase aktivitas siswa pada kelas eksperimen dan kelas kontrol adalah 91,66% dan 60,03%. Persentase ketuntasan siswa secara klasikal pada kelas eksperimen dan kelas kontrol adalah 75,00% dan 18,75%. Uji-t digunakan untuk menguji perbedaan rata-rata hasil belajar siswa antara kelas kontrol dan kelas eksperimen. Hasil uji-t diperoleh thitung = 7,22>ttabel = 1,67 dengan Î± = 5% dan dk=66 sehingga rata-rata hasil belajar siswa kelas eksperimen lebih baik daripada kelas kontrol. Berdasarkan hasil tersebut dapat disimpulkan bahwa penerapan metode Example Non Example efektif untuk meningkatkan aktivitas dan hasil belajar siswa pada materi Keanekaragaman Hewan di SMP N 2 Tengaran Kabupaten Semarang. Â